Alex & I: In proximity to the Other of politics - Sumugan Sivanesan (Law Text Culture, 2014)
For a brief period of time Sanjeev ‘Alex’ Kuhendrarajah gained international notoriety as the self-styled spokesperson for 254 Sri Lankan Tamils who refused to disembark from a small wooden cargo boat, KM Jeya Lestari 5, docked off the Indonesian port of Merak from October 2009. The boat, which was detected by Australian authorities while floundering in international waters off the Sunda Strait, was intercepted by the Indonesian navy at the request of the then Australian prime minister, Kevin Rudd. The charismatic asylum seeker, who introduced himself as Alex at a dockside press conference, quickly became a favourite with journalists for his command of English and his ‘raw and defiant’ manner (Allard 2009).